Analisis potensi effort dan Inisiatif dan pengaruhnya terhadap Job performance dengan variabel mediasi Moral of job pada Pondok Pesantren Riyadlul Jannah Mojokerto - Budiyono Santoso (FADZAT: Jurnal Ekonomi Syariah, 2021)
Organizations need to encourage their employees to have high job performance in the hope of getting a lot of benefits for the organization, but not making employees feel disadvantaged. This condition is strongly influenced by the role of a leader in the organization, initiatives and employee development. The aims of this study are: 1) To determine and analyze the effect of effort on Moral of job. 2) To find out and analyze the effect of initiative on Moral of job. 3) To find out and analyze effort on job performance. 4) To find out and analyze the effect of initiative on job performance. 5) To find out and analyze the effect of Moral of job on job performance. 6) To find out and analyze effort on job performance with the mediating variable Moral of job. 7) To find out and analyze the effect of initiative on job performance with the mediating variable Moral of job. Based on considerations of time, effort, and funds, as well as the scope of the problem and the large number of subjects in a population of 336 people, this study uses the Slovin formula with a significance (p) (0.1) so that a sample of 79 people is determined. Where all members of the population are sampled, the data analysis tool uses the SmartPLS software version 3.3.7. From the results of the study, it can be concluded as follows: 1) effort has a significant effect on Moral of job 2) Initiative has no effect on Moral of job 3) Effort has no effect on Job performance 4) Initiative has a significant effect on Job performance 5) Moral of job has no effect on Job performance 6) effort has an indirect effect on Job performance through Moral of job 7) Initiative has an indirect effect on Job performance through Moral of job.